2007
DOI: 10.1116/1.2750343
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sensing characteristics and mechanism of Pd∕AlGaN∕GaN Schottky diodes subjected to oxygen gettering

Abstract: Hydrogen sensing characteristics in vacuum and in air were investigated on Pd Schottky diodes that were formed on AlGaN / GaN two-dimensional electron gas wafer and subjected to a surface control process for oxygen gettering. By applying the surface control process, leakage currents in Pd/ AlGaN / GaN Schottky diode were greatly reduced. Such diodes showed high hydrogen detection sensitivities and fast turn-on and -off characteristics in air, although they showed very slow turn-off behavior in vacuum. From det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…2-5 can be explained by the sensing mechanism discussed in detail previously [9]. Namely, the current increase is due to reduction of Schottky barrier height (SBH) caused by interface dipole formed by atomic hydrogen that is generated by dissociation of hydrogen molecule on the catalytic Pd …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…2-5 can be explained by the sensing mechanism discussed in detail previously [9]. Namely, the current increase is due to reduction of Schottky barrier height (SBH) caused by interface dipole formed by atomic hydrogen that is generated by dissociation of hydrogen molecule on the catalytic Pd …”
Section: Resultsmentioning
confidence: 97%
“…Schottky barrier height reduction by interface dipole formation through adsorption of atomic hydrogen [9].…”
mentioning
confidence: 99%
“…For example, diodes prepared in situ to avoid oxide interfacial layers showed very poor response to hydrogen [28] and the incorporation of a SiO 2 layer to form a metal-oxide-semiconductor structure was found to greatly enhance the sensing response [22]. However, others have reported that when surface oxide concentrations were minimized on AlGaN/GaN Schottky diodes, the hydrogen detection sensitivity increased [19]. In our case, Auger Electron Spectroscopy showed similar amounts of interfacial oxygen in our a-plane diodes compared to the c-plane devices.…”
Section: Methodsmentioning
confidence: 92%
“…This property gives the promise for high-power and high-temperature microwave applications. Moreover, a high density of 2DEG is beneficial to the sensitivity of surface condition and thus can be used to improve the hydrogen sensing capability [16]. Recently, on the other hand, the SiO 2 passivation has been employed in the AlGaN/GaN high electron mobility transistor (HEMT) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbed hydrogen atoms at Pd/SiO 2 interface are polarized to form hydrogen dipoles by the internal electric field. Thus, hydrogen dipoles cause the lowering effect of Schottky barrier height, and substantially increase the response current [16]. The device parameters can be extracted from the thermionic emission mechanism [21]:…”
Section: Introductionmentioning
confidence: 99%